Concurrent Hepsin overexpression and adenomatous polyposis coli deletion causes invasive prostate carcinoma in mice. Issue 14 (2nd July 2015) - Valkenburg, Kenneth C.; Hostetter, Galen; Williams, Bart O.
<x xml:space="preserve">Abstract</x> BACKGROUND A clinical need to better categorize patients with prostate cancer exists. The Wnt/β‐catenin signaling pathway plays important roles in human prostate cancer progression. Deletion of the endogenous Wnt antagonist adenomatous polyposis coli (Apc) in mice causes high grade prostate intraepithelial neoplasia, widely thought to be the precursor to prostate cancer. However, no metastasis occurrs in this model. New mouse models are needed to determine molecular causes of tumorigenesis, progression, and metastasis. METHODS To determine whether the overexpression of the prostate oncogene Hepsin could cause prostate cancer progression, we crossed a prostate‐specific Hepsin overexpression model to a prostate‐specific Apc‐deletion model and classified the observed phenotype. RESULTS When Apc was deleted and Hepsin overexpressed concurrently, mice displayed invasive carcinoma, with loss of membrane characteristics and increase of fibrosis. These tumors had both luminal and basaloid characteristics. Though no metastasis was observed, there was evidence of adenomas and lung necrosis, inflammation, and chronic hemorrhage. CONCLUSIONS This work indicates that the Wnt/β‐catenin pathway and the Hepsin pathway act in concert to promote prostate cancer progression. Both of these pathways are up‐regulated in human prostate cancer and could represent chemotherapeutic targets. Prostate 75:1579–1585, 2015. © 2015 Wiley Periodicals, Inc.